2001
DOI: 10.1177/09680519010070020901
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acyl chain fluidity on the lipopolysaccharide-induced activation of complement

Abstract: Lipopolysaccharides (LPSs, endotoxins) are the major amphiphilic constituents of the outer leaflet of the outer membrane of Gram-negative bacteria. They are known to activate the complement cascade to form lytic membrane pores. Here, we study the influence of the fluidity of the acyl chains of LPSs and lipid As on the formation of lytic pores. To this end, we have performed electrical measurements on asymmetric planar endotoxin/phospholipid bilayers as a reconstitution model of the outer membrane using two dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
4
1
Order By: Relevance
“…It has been shown earlier that an increase in membrane fluidity increases the formation of lytic membrane pores by the complement system (27). However, this parameter cannot explain the positive correlation between pore formation and the length of the core sugar moiety, because membrane fluidity varies only slightly for the LPS used in the present investigation (28).…”
Section: Fig 5 Mean Number Of Porescontrasting
confidence: 45%
“…It has been shown earlier that an increase in membrane fluidity increases the formation of lytic membrane pores by the complement system (27). However, this parameter cannot explain the positive correlation between pore formation and the length of the core sugar moiety, because membrane fluidity varies only slightly for the LPS used in the present investigation (28).…”
Section: Fig 5 Mean Number Of Porescontrasting
confidence: 45%
“…This, coupled with data indicating that decreased LPS acylation results in increased membrane permeability in phospholipid bilayers, suggests a model in which the addition of an acyl group to the lipid A region increases the rigidity of the membrane, thus decreasing the susceptibility to lysis by various immune mechanisms (21).…”
Section: Discussionmentioning
confidence: 93%
“…This suggests that the lipid A acylation state may influence outer membrane permeability. In addition, changes in lipid A acylation have been shown to affect complement activation and opsonization, as well as TLR-4 recognition in vitro (1,7,13,21). Despite these compelling data, the influence of lipid A acylation on in vivo host-pathogen interactions is not well understood.…”
mentioning
confidence: 94%
“…We could on the one hand determine the activation pathway and on the other hand investigate the influence of the lipid matrix on the pore size. 27,66,67 Whereas no changes in electrical conductance were detected when serum was added to the PL side of the membrane, serum addition to the LPS side (Re LPS from Salmonella enterica sv. Minnesota or Escherichia coli) led to an increase in membrane conductance.…”
Section: Complementmentioning
confidence: 99%
“…This correlation was also shown to hold for the susceptibility of a respective pair of rough mutant strains towards human serum. 67 The influence of fluidity on complement activation has been discussed controversially so far; however, the data have been derived from systems which did not closely resemble the outer membrane. 69,70 In studies aimed at the elucidation of the pathways of complement activation, we found that neither the Ca 2+chelator EGTA nor the depletion of C1q had an influence on the activation by GSL-1, whereas in the case of Re LPS a significant de-activation was observed.…”
Section: Complementmentioning
confidence: 99%